Preparation and properties of a novel anode of interpenetrating phase composite structure - Park, J. -Y.; Lee, J. -H.; Kim, J.; Lee, H. -W. (TRANS TECH PUBLICATIONS LTD, 2006)
A novel Ni-YSZ anode with interpenetrating phase composite (IPC) structure was developed using NiO-YSZ core-shell composite powder and evaluated in terms of microstructure, electrical conductivity, thermal expansion and flexural strength. In comparison to conventional anode, the anodic performance of IPC anode appeared to be more desirable for improving structural reliability of SOFC unit cells and stacks. This study reveals that the anodic performance of IPC anode can be readily tailored by controlling core-shell composite powder particles.
Keywords: METAL-CERAMIC COMPOSITES; OXIDE FUEL-CELLS